Utilization of Voice Recognition in the Development of Android-Based Medical Emergency Response Applications - Suryaningsih Patandung; Yohanis Padallingan; Srivan Palelleng; Plesmi Plesmi; Lisna Junita Pairunan (Lembaga Pengembangan Kinerja Dosen, 2025)
Medical emergencies can occur at any time and often without warning. Conditions such as heart attacks, strokes, seizures, or severe accidents require immediate assistance from others. However, many victims are unable to request help due to physical limitations and delays in accessing emergency services, especially among the elderly and people with disabilities. Along with technological advances, medical emergency response systems can be developed through Android-based applications. Limited mobility in emergency situations makes voice recognition technology a suitable solution, using common emergency voice commands such as “help” or “pain.” This study aims to design and implement an application capable of rapidly sending emergency alerts through an emergency button or voice command activation, while also displaying the user's real-time location using Google Maps. The system was developed using the Waterfall method, which includes requirements analysis, system design, implementation, testing, and maintenance. Application testing was conducted using black-box testing to evaluate functionality and a User Acceptance Test (UAT) involving 15 respondents based on a Likert scale. The results indicate that all application features function properly, with a user acceptance level of 91.44%, categorized as very good. Therefore, the Tolong Kini application is considered effective and beneficial in supporting faster medical emergency response.